DIGITAL TECHNOLOGY AND EDUCATION : mapping productions in scientific journals - Lima Santos, Willian; Lucas Vieira, André Ricardo; de Vasconcelos, Carlos Alberto (Revista Ciências Humanas, 2021)
This study aimed to map the productions on technologies and education in scientific journals, from 2006 to 2019.The methodological path that composed the results found, from the most cited texts in Google Scholar of journals Tempos e Espaços em Educação, Espaço Pedagógico e Tear: Revista de Educação, Ciência e Tecnologia,was guided by the systematic review, which is a type of research that follows specific standards and aims to give logic to a wide documentary corpus. In this sense, applied the exclusion/inclusion criteria it was found that the studies with greater notoriety are concentrated in the areas of teacher training and practice from the use of technologies, in addition to inclusion and digital culture. Through the mapping, it was possible to perceive the significant increase in productions on digital technologies in the investigated journals, contributing to the improvement of professionals and researchers who make investigations in this area of knowledge and, in addition, express the relevance of technologies and their varied possibilities of use in the educational field. Despite technological advances, access to the network, lack of resources and failures in teacher training for the use of digital, there are still some obstacles that interfere in the integration of digital technologies in education.